PENERAPAN METODE BELAJAR AKTIF DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA SD NEGERI - Karimah, Ummah; Fadhilah , Sahra; Yoga Saputra, Aldian; Alghifari , Abizar; Umam, Chairul (Rumah Riset Publisher, 2025)
In this modern era, the learning process of memorizing the Qur'an is faced with various challenges. Students often feel bored and have difficulty in memorizing the Qur'an with traditional methods. Therefore, innovative and interesting learning methods are needed so that students can memorize the Qur'an more easily and enjoyably. Improving the memorization of the Quran is a very important thing in the life of a Muslim. The process of memorizing the Quran not only involves the ability to remember words, but also requires perseverance, consistency, and high dedication. Various studies have been conducted to understand the best way to improve Quran memorization. The purpose of this study is to find out how the strategy of applying active learning methods in improving the memorization of the Qur'an of State Elementary School students. This research uses qualitative, data collection with primary data from Islamic Religious Education Teachers at SDN Grogol Selatan 09. This research collects data through interviews and observations. The result of this study is to show that the application of active learning methods not only improves students' memorization ability, but also increases their motivation and interest in learning. In addition, this approach is also proven to help in the development of students' social and cognitive skills. This research is expected to make a significant contribution in the development of Islamic religious education curriculum in primary schools as well as offering an alternative learning method that is more effective and fun.